Faire tourner Paris : ethnogénétique et logogénétique de Nana de Zola - Sophie Ménard (Flaubert: Revue Critique et Génétique)
By identifying, in the preliminary stages of Nana, the particular composition of the cultural specifications of an “upside-down life”, this article examines the narrativisation of an idiomatic expression reconfigured by the scriptural work: “Nana turning society around just like a woman makes milk turn sour”. Picking up a common belief, the dangerous force of menstruation, the “avant-textes” renew and integrate in the narration the folkloric imagination of feminine physiology, in particular women’s “red period”. Nana appears, from her birth, physiologically and symbolically, crooked. Her textual destiny will be to upturn Paris by decaying and bloodying it with her deregulated sex. This embryonic story condenses a cultural microsystem which creates and structures one of the novel’s symbolic systems.